The education as a tool to eradicate the female genital mutilation (Revista Innova Educación, 2020)
This article was elaborated to illustrate the use of education as a tool to eradicate the female genital mutilation. The current text was structured doing an introduction about the theme, presenting results about general aspects of the female genital mutilation, the education as an agent to change societies and the educational process as a catalyst to eliminate such practice. Due to this, a qualitative documental investigation was constructed, concluding that this procedure brings physical and psychic consequences on women, and it is through the leaning that this reality can be changed to promote respect to the human rights.
Keywords: Education.; women; genital mutilation; eradication.